National Digital Transformation Policy: Fundamental aspects to guarantee digital equity - Chocobar Reyes, Marushka (2022)
For some years, Peru has started a determined push towards a national process of digital transformation that guarantees access to the opportunities of the digital environment for all people. This process has been accelerated by the demand for change and the disruption generated by the health crisis and, in turn, by the citizen’s decision to incorporate digital into their daily lives. The National Digital Transformation Policy emerges as a guiding document with the purpose of promoting digital citizenship, guaranteeing equitable and safe access to digital transformation and what determines the actions of the country’s Digital Agenda towards 2030. This article addresses those aspects of this Policy that will constitute the critical success factors to guarantee digital equity.